2022
DOI: 10.1038/s41591-022-01960-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-infusion CAR TReg cells identify patients resistant to CD19-CAR therapy

Abstract: Approximately 60% of patients with large B cell lymphoma treated with chimeric antigen receptor (CAR) T cell therapies targeting CD19 experience disease progression, and neurotoxicity remains a challenge. Biomarkers associated with resistance and toxicity are limited. In this study, single-cell proteomic profiling of circulating CAR T cells in 32 patients treated with CD19-CAR identified that CD4 + Helios + CAR T cells on day 7 after infusion are associated with progressive disease and less severe neurotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 75 publications
5
96
1
Order By: Relevance
“…Recently, it has further been shown that T reg /chimeric antigen receptor T-cell ratios in favor of T reg impair the therapeutic efficacy of chimeric antigen receptor T cells. 6 This highlights the complexity of the T reg compartment within chronic inflammatory diseases including cancer. Consequently, T reg are extensively studied as targets for immunotherapies with the aim to reduce immunosuppression by tumorinfiltrating T reg and to promote antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has further been shown that T reg /chimeric antigen receptor T-cell ratios in favor of T reg impair the therapeutic efficacy of chimeric antigen receptor T cells. 6 This highlights the complexity of the T reg compartment within chronic inflammatory diseases including cancer. Consequently, T reg are extensively studied as targets for immunotherapies with the aim to reduce immunosuppression by tumorinfiltrating T reg and to promote antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The other side of this coin is that T reg suppressive activity in solid tumors is generally associated with reduced antitumor responses. Recently, it has further been shown that T reg /chimeric antigen receptor T‐cell ratios in favor of T reg impair the therapeutic efficacy of chimeric antigen receptor T cells 6 . This highlights the complexity of the T reg compartment within chronic inflammatory diseases including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Given the nature of our question, the role of chronic CAR stimulation on T cell dysfunction, we prioritized sequencing of cells undergoing chronic stimulation for a prolonged period. Most studies evaluate CAR T cells collected between days 7-30 after infusion ( 41, 42 ), or cells collected at later time points from patients with durable responses, a clinical setting in which CAR T cells are not chronically stimulated and persist longer ( 37, 43 ). To our knowledge, this is the first study to report data on CAR T cells isolated months after infusion from a patient with progressive lymphoma, a scenario in which CAR T cell persistence is highly limited beyond 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to phosphatidylinositol-3-kinase (PI3K) inhibitors during the CAR-T manufacturing process can improve T-cell fitness and reduce T-cell exhaustion, and bb21217 incorporated PI3K inhibition during the manufacturing of bb2121 (equivalent to ide-cel) with this goal in mind ( 65 , 66 ). Although bb21217 is no longer under development, a more recent publication has suggested that the transduction of regulatory T cells (T reg ) with CARs predicts shorter responses to CD19-directed CAR-T therapy ( 67 ). Because PI3K inhibitors are known to suppress T reg cells ( 68 ), future research may shed additional insights on the merits of T reg manipulation.…”
Section: Better Mileage: Longer Duration Of Responsesmentioning
confidence: 99%